Associations between body mass index, high-sensitivity C-reactive protein, and depressive symptoms: NHANES 2015-2016 - Zhang, Yan; Zhen, Fengya; Zhang, Yaxing; An, Cuixia (Frontiers in Psychiatry, 2025)
ObjectiveStudies have shown associations between Body Mass Index (BMI), High-Sensitivity C-reactive protein (HSCRP), and depressive symptoms(DP). However, the complex relationship between them remains uncertain. The objective of this research is to examine the correlation between them in a substantial sample that is representative of the national level.MethodsOur analysis was based on the 2015-2016National Health and Nutrition Examination Survey (NHANES).DP was measured by the Patient Health Questionnaire-9 (PHQ-9). Using multivariable logistic regression analysis and stratified analysis, we examined the relationship between BMI, HSCRP, and DP. We applied generalized additive models to explore the non-linear relationships among variables.ResultsThis study included a total of 4834 participants. The results revealed that BMI (P=0.002) and HSCRP (P=0.008) were risk factors for DP. The relationship between BMI and DP (P=0.035), BMI and HSCRP (P<0.001) were non-linear. The nonlinear association between HSCRP and DP (P=0.031), BMI and DP (P=9e-04) is significant in females when stratified by gender. No nonlinear association was found between BMI and DP (P =0.677) and between HSCRP and DP (P =0.439) in males. The results of the interaction test reveal a significant interaction between HSCRP and gender.ConclusionsResearch has found both BMI and HSCRP are risk factors for DP and the relationship between them was non-linear. The nonlinear associations between BMI and DP, as well as between HSCRP and DP, are gender-dependent.